ANALISIS SIKAP DAN NIAT MEMBELI KAUM MUDA DI SURAKARTA TERHADAP PAKAIAN BATIK - Kussudyarsana Kussudyarsana (Benefit: Jurnal Manajemen dan Bisnis, 2006)
In recent time, Batik, as a traditional fashion not fully intention to the youth market. The Youthmarket, are very potential market that profitable for Batik Fashion Industry. This research try toanswer the question about attitude and intention to buy of the young people toward batik. The authorpredict negative attitude but positive normative belief effect intention to buy of young people towardBatik. This research uses non-random sampling method (convenience sampling) in order to collect data.One hundred young people are used as respondent. Majority of those respondents are student inuniversity. Data were collected using self-administrative questionnaire. The result suggested model notfully confirm to reason action theory, because normative belief did not effect toward intention to buy.However, attitude had effect toward intention to buy. The study result could be taken into account anypolicies that link the all of characteristic used the study.